Occurrence of acrylamide in selected food products - Bušová, Milena; Bencko, Vladimír; Kromerová, Katarína; Nadjo, Iris; Babjaková, Jana (Central European Journal of Public Health, 2020)
OBJECTIVE: Acrylamide is a toxic compound found in occupational and non-occupational environment. It originates from industrial use, technological processes in construction as well as food production, water purification, and laboratory use. Adverse effects including neurotoxicity, probably carcinogenicity, genotoxicity, teratogenicity, and reproductive toxicity were reported in many studies. Our study is focused on acrylamide content in selected food products in the Czech Republic. METHOD: In this study, we determined acrylamide content in selected samples of commonly consumed food products (potato chips, biscuits, popcorn, corn flakes, breakfast cereals, and baked muesli). RESULTS: The concentration of acrylamide in most samples of potato chips, biscuits and popcorn exceeded the benchmark limits. The acrylamide content in samples of potato chips from one manufacturer in 4 cases out of 5 analysed samples exceeded benchmark limit. On the other hand, no corn flakes sample acrylamide content from the same manufacture exceeded the benchmark limit. With 20 of all analysed samples exceeding the benchmark levels for acrylamide, it can be concluded that 47.6% of samples did not comply with the benchmark level. CONCLUSION: Dietary intake of frequently consumed food products with the acrylamide content exceeding the recommended comparative value could have adverse effects on the human health. Our study confirmed high amount of acrylamide in some selected food samples. The reduction of dietary burden with acrylamide is possible by complying with the correct technological principles in food preparation.
Keywords: Česká republika; Food Analysis; dieta; kontaminace potravin; manipulace s potravinami; lidé; analýza potravin; Diet; Czech Republic; Food Handling; Acrylamide; Food Contamination; akrylamid; Humans